Reliability of Using Elastic Modulus for Non-Homogeneous Materials - Khan Rimsha (MATEC Web of Conferences, 2016)
This paper investigates the literature available for derivation of the elastic modulus (E) as employed specifically in non-homogenous materials. There is a big pool of E-values in the literature which user can pick and use. However their reliability is still a question. This study will therefore focus on the values of elastic modulus acquired from the secondary databases and their reliability in numerical methods like Finite Elements (FE). This study uses E-values obtained from bones, muscles and tissues. Bone is a composite material with a very intricate internal geometry. Acquiring the elastic modulus values for irregular geometries like bones is not a straight forward process. This study therefore compares the different studies provided in literature for derivation of elastic properties of bones from different vertebrates and investigates the reason of variations. The study infers that populating all the values of elastic modulus without a standard procedure, creates a level of ambiguity that bars the understanding of the use of modulus of elasticity where insightful procedures are in question for example finite element analysis of sensitive materials . Therefore there is a need to take great care in deriving the values of E.